Key account management in business-to-business relationship: identifying top K persuaders using singular value decomposition - Ahmmed, Kawsar; Mohd Noor, Nor Azila (Korea Distribution Science Association, 2016)
Purpose - Key account management is a supplier company initiated relational approach that has received great attention from both academics and practitioners manifested in the business-to-business relationship literatures. However, there is widespread debate and contention on what should be the underlying theoretical base for defining this vital part of relationship marketing. With the insights from the social exchange theory, present paper explores how social exchange affects the dynamic nature of key account management relationship at the organizational level.Research design, data, and methodology - The paper follows a comprehensive review approach to examine the relationship between social exchange theory and key account management approach. Conceptual arguments and findings are assessed across studies with the main objective of showing how social exchange theory develops the governance mechanism in maintaining the key account relationship.Results - Since relational norm is considered as a glue for the maintenance of buyer-seller relationship in social exchange theory, factors develop the non-contractual governance mechanism ‘relationship’ in business-to-business relationship and this norm replaces or supplements more formal governance mechanisms such as contracts are explored.Conclusions - This paper advances central relational norm to manage the company’s most important key customers and demonstrates how this norm can be developed in buyer-seller key account relationship.Implications from this new perspective are forwarded.